PROFITABILITY DETERMINANTS OF VIETNAMESE COMMERCIAL BANKS Is efficiency an important factor? - Nguyen, Tra Hoang (2014)
This paper empirically analyses the factors that determine the profitability for an example of 31 Vietnamese commercial banks during the period of 2006-2013. It is concludes that the high bank profitability during this studied period is associated with high economic growth, larger percentage of customer deposit, small board size and good technical efficiency. Yet, there was no evident supporting the market power hypothesis. Finally the u-shape relationship between size and profitability was found which prove the existent of a threshold of scale economies.